2008
DOI: 10.1126/science.1163113
|View full text |Cite
|
Sign up to set email alerts
|

Trampoline Effect in Extreme Ground Motion

Abstract: In earthquake hazard assessment studies, the focus is usually on horizontal ground motion. However, records from the 14 June 2008 Iwate-Miyagi earthquake in Japan, a crustal event with a moment magnitude of 6.9, revealed an unprecedented vertical surface acceleration of nearly four times gravity, more than twice its horizontal counterpart. The vertical acceleration was distinctly asymmetric; the waveform envelope was about 1.6 times as large in the upward direction as in the downward direction, which is not ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 12 publications
3
68
0
Order By: Relevance
“…(3) Kinematic inversion of the strong motion data (Holden 2011) suggests that the direction of the rupture was northwestward and upwards, towards Christchurch city, potentially producing directivity effects (Holden 2011). (4) Complex behaviour of the near-surface soil layers, described by Fry et al (2011b), who noted that several records in Christchurch city show asymmetry in the acceleration records, similar to that previously observed in Japan by Aoi et al (2008) and Yamada et al (2009). Fry et al (2011b) concluded that the soil's behaviour may have increased upward accelerations, in a so-called 'trampoline effect'.…”
Section: Aftershock Activity Between 4 September 2010 and February 2011supporting
confidence: 55%
“…(3) Kinematic inversion of the strong motion data (Holden 2011) suggests that the direction of the rupture was northwestward and upwards, towards Christchurch city, potentially producing directivity effects (Holden 2011). (4) Complex behaviour of the near-surface soil layers, described by Fry et al (2011b), who noted that several records in Christchurch city show asymmetry in the acceleration records, similar to that previously observed in Japan by Aoi et al (2008) and Yamada et al (2009). Fry et al (2011b) concluded that the soil's behaviour may have increased upward accelerations, in a so-called 'trampoline effect'.…”
Section: Aftershock Activity Between 4 September 2010 and February 2011supporting
confidence: 55%
“…Çelebi et al Net, 1996), KiK-net (KiK-net, 2000), and Japan Meteorological Agency instrumentation. After an interval of 23 yrs, the largest recorded PGA increased by about a factor of 2 in 2008 (Aoi et al, 2008). A larger number of seismic instrumentation makes a record of PGA in excess of one previously recorded more likely.…”
mentioning
confidence: 95%
“…However, the probability of a future PGA greater than 40 m=sec 2 is only 10% in the next 50 yrs, assuming a steady increase in station density of 5% of ρ 0 per year. Aoi et al (2008) and Yamada et al (2009) proposed a physical mechanism for extremely large vertical accelerations. This may explain future records with PGAs much larger than the current, largest recorded PGA.…”
mentioning
confidence: 99%
“…In particular, maximum PGA's in the vertical component of 2.21g and 1.88g were observed at HVSC and PRPC, respectively. The vertical acceleration time histories at these two sites are also inferred to exhibit the so-called 'trampoline effect' [11,12] caused by separation of surficial soil layers in tension, limiting peak negative vertical accelerations to approximately -1g. As discussed subsequently, the ground motion at PRPC also experienced significant forward directivity effects which are evident in the long-period content of the fault normal component in Figure 4a.…”
Section: Extreme Ground Motionsmentioning
confidence: 99%